Life Balance in the Tafsir of Al-Misbah and Ibn Kathir - Afifatun Nisa Hasibuan; Arifinsyah (al-Afkar, Journal For Islamic Studies, 2025)
This research explores the concept of balanced living ("keseimbangan hidup") within Islam through a comparative analysis of Tafsir Al-Mishbah by M. Quraish Shihab and Tafsir Ibn Kathir. Employing a qualitative descriptive method with a thematic interpretive approach, the study examines how both interpretations address the multifaceted aspects of a balanced life. The analysis reveals points of convergence and divergence, particularly concerning the balance between worldly and otherworldly pursuits, the integration of physical, intellectual, and spiritual dimensions, and the responsibilities towards oneself, others, and the environment. This comparative study contributes to a richer understanding of the Islamic concept of balanced living by highlighting the nuanced perspectives offered by these two influential tafsirs.